2022
DOI: 10.3389/fmed.2022.978272
|View full text |Cite
|
Sign up to set email alerts
|

Third dose of anti-SARS-CoV-2 inactivated vaccine for patients with RA: Focusing on immunogenicity and effects of RA drugs

Abstract: ObjectivesTo evaluate the immunogenicity of the third dose of inactivated SARS-CoV-2 vaccine in rheumatoid arthritis (RA) patients and explore the effect of RA drugs on vaccine immunogenicity.MethodsWe recruited RA patients (n = 222) and healthy controls (HC, n = 177) who had been injected with a third dose of inactivated SARS-CoV-2 vaccine, and their neutralizing antibody (NAb) titer levels were assessed.ResultsRA patients and HC were age- and gender-matched, and the mean interval between 3rd vaccination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These findings were supported by data from a Chinese cohort study involving RA patients, which showed that patients treated with bDMARDs, JAKis and prednisone had significantly lower neutralizing antibody titers when compared with healthy controls [42]. However, no significant decrease was observed in RA patients treated with csDMARDs [42].…”
Section: Baseline Glucocorticoids Negatively Impact Covid-19 Outcomesmentioning
confidence: 61%
See 1 more Smart Citation
“…These findings were supported by data from a Chinese cohort study involving RA patients, which showed that patients treated with bDMARDs, JAKis and prednisone had significantly lower neutralizing antibody titers when compared with healthy controls [42]. However, no significant decrease was observed in RA patients treated with csDMARDs [42].…”
Section: Baseline Glucocorticoids Negatively Impact Covid-19 Outcomesmentioning
confidence: 61%
“…This reduction was attributed to a faster decline in antibody levels, indicating a significantly reduced duration of vaccination-induced immunity compared with healthy controls or patients receiving csDMARDs [41].Furthermore, there was a reduced response to booster vaccination, highlighting the need for earlier booster vaccination strategies based on specific antibody levels in patients under b/tsDMARD therapy [41]. These findings were supported by data from a Chinese cohort study involving RA patients, which showed that patients treated with bDMARDs, JAKis and prednisone had significantly lower neutralizing antibody titers when compared with healthy controls [42]. However, no significant decrease was observed in RA patients treated with csDMARDs [42].…”
Section: Baseline Glucocorticoids Negatively Impact Covid-19 Outcomesmentioning
confidence: 80%
“…The abrogated immunological response to the primary vaccination schedule results in a faster decline of post-vaccination immunity in IA patients [ 5 , 7 , 16 , 18 , 25 , 26 ], making booster vaccinations among IA patients even more important than in HC. Current studies proved that, though COVID-19 booster vaccinations are effective in IA patients [ 27 , 28 , 29 ], also the immunogenicity of the booster dose is impaired in this group of patients [ 15 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. There are only single studies evaluating the effect of immunomodulatory drugs on the immunogenicity of the booster dose against COVID-19, indicating worsen response after GCs [ 30 ], biological and targeted synthetic disease-modifying antirheumatic drugs (bDMARDs and tsDMARDs) [ 15 , 30 ], and MTX [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies proved that, though COVID-19 booster vaccinations are effective in IA patients [ 27 , 28 , 29 ], also the immunogenicity of the booster dose is impaired in this group of patients [ 15 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. There are only single studies evaluating the effect of immunomodulatory drugs on the immunogenicity of the booster dose against COVID-19, indicating worsen response after GCs [ 30 ], biological and targeted synthetic disease-modifying antirheumatic drugs (bDMARDs and tsDMARDs) [ 15 , 30 ], and MTX [ 34 , 35 ]. In our previous study, we assessed the effect of immunomodulatory drugs on humoral and cellular responses after the booster dose [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. patients (6)(7)(8), also the immunogenicity of the booster dose is impaired in this group of patients (9)(10)(11)(12). In our previous study, we assessed humoral and cellular responses before the booster dose (more than 6 months from the primary vaccination schedule; T0) and 4 weeks after the booster dose (T1) in 49 IA patients and 47 HC vaccinated at the COVID-19 vaccination unit in a rheumatology center (13).…”
mentioning
confidence: 99%